Unraveling the effect of the hydration level on the molecular mobility of nanolayered polymeric systems - Borges, J. (2015)
This work investigates the influence of the hydration level on the molecular mobility and glass transition dynamics of free-standing chitosan/alginate (CHT/ALG) nanolayered systems. Non-conventional dynamic mechanical analysis identified two relaxation processes assigned to the α-relaxation of the two biopolymers, respectively CHT and ALG, when immersed in water/ethanol mixtures. This phenomenon explains the shape memory properties of the multilayered systems induced by hydration, thus constituting promising smart materials that would be of paramount importance in a plethora of research fields, including in the biomedical and biotechnological fields.